Analisis Perilaku Konsumen Dalam Keputusan Pembelian Sepeda Motor Yamaha CV Tjahaja Baru Lubuk Buaya Padang - Khairil Azmi (Jurnal Ekonomi, Bisnis dan Manajemen, 2022)
Public demand for motorcycles is always increasing. The motorcycle manufacturers compete with each other to offer their products. Yamaha is one of the largest and most excellent automotive companies, especially in Indonesia. In the current uncertain economic situation due to the Covid-19 pandemic crisis, this has resulted in sluggishness in motorcycle sales. So that before marketing their products, companies need to pay attention to consumer behavior first. Because consumer behavior will be the target for purchasing products to be marketed. The purpose of the study was to analyze consumer behavior in deciding to purchase a Yamaha motorcycle at CV Tjahaja Baru Lubuk Buaya Padang. This study uses qualitative methods and belongs to field research with semi-structured interviews and documentation as data collection techniques. The findings from this study are that prospective motorcycle consumers in buying a motorcycle take a lot of considerations to get the motorcycle they want, what are the advantages of a motorcycle, an affordable price, if purchased on credit with low interest and so on.